SD OCT retinal thickness in the macula area in premature children who received laser photocoagulation of avascular retina for severe ROP (Ukrainian Journal of Ophthalmology, 2025)
Background: Immature ocular optics at birth and severe retinopathy of prematurity (ROP) may affect normal development of the retina and lead to late impairment of visual functions.Purpose: To compare spectral-domain optical coherence tomography (SD OCT) retinal thickness in the macular area between premature children who received laser photocoagulation of avascular retina (LPCAR) and full-term children aged 4-6 years.Materials and Methods: Twenty-five premature children (50 eyes) and 38 full-term control children (69 eyes without eye disease) aged 4-6 years received observation care at the Filatov institute between 2011 and 2017. The inclusion criterion for premature children was receiving LPCAR for severe (type 1 subthreshold, or threshold) ROP diagnosed during screening. Patients with grade 4 or 5 ROP or other ocular pathology (history of cataract, glaucoma, trauma or eye surgery) were excluded. Results: There was a significant difference in retinal thickness in the macular area between premature and full-term children; the magnitude of the difference depended on the severity of ROP. The foveal-to-central thickness ratio was found to be increased compared to controls by at least 0.1 in 18 premature children (36 eyes, 72%) who received LPCAR (p
Keywords: retinopathy of prematurity; retinal thickness; SD OCT; smooth foveal depression